From global trends to local realities: understanding women's political involvement for Indonesia's democratic progress - Dzinnun, Yusriah; Jubba, Hasse; Azhar, Muh; Qodir, Zuly (Department of Government Studies, Universitas Muhammadiyah Makassar, 2024)
The urgency of this research lies in the need to understand the trends, contributions, and dynamics of women's political participation globally. This article aims to map studies that focus on women's political participation. Research methods include bibliometric analysis with data sources from the Scopus database. The study's findings reflect significant growth in women's political participation research, especially in recent years, with distribution varying by country and research theme. The research findings also show that although there are themes that have received attention, there are still areas that need to be explored further, such as intersectionality, gender equality, gender, and the impact of social media that provide insight into the complexity of women's political participation issues. This study recommends the need for increased research and local understanding of the factors influencing women's political participation in Indonesia to strengthen women's role in politics by learning from other countries that have successfully implemented inclusive policies. In addition, by involving various parties, including the government, research institutions, and civil society, Indonesia can create an environment that supports, empowers, and encourages women's political participation optimally. The implications of these findings not only help shape academic discourse, but also lay the foundation for concrete efforts to achieve gender equality and women's empowerment in the wider political sphere.